2016
DOI: 10.7717/peerj.2429
|View full text |Cite
|
Sign up to set email alerts
|

Prevention of necrotizing enterocolitis with probiotics: a systematic review and meta-analysis

Abstract: ContextNecrotizing enterocolitis (NEC) is the most frequent gastrointestinal emergency in neonates. The microbiome of the preterm gut may regulate the integrity of the intestinal mucosa. Probiotics may positively contribute to mucosal integrity, potentially reducing the risk of NEC in neonates.ObjectiveTo perform an updated systematic review and meta-analysis on the efficacy and safety of probiotics for the prevention of NEC in premature infants.Data SourcesStructured searches were performed in: Medline, Embas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
108
1
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 120 publications
(118 citation statements)
references
References 77 publications
(157 reference statements)
5
108
1
2
Order By: Relevance
“…In hospital settings, recognition of the value of beneficial microbes is happening, with use of probiotics to reduce mortality and morbidity of low-birth-weight premature babies (Sawh et al 2016) (including in London, Ontario, after 10 years of advocating) and to prevent antibiotic-associated diarrhea including Clostridium difficile infections (Hickson et al 2007;Maziade et al 2015), albeit not all studies have shown efficacy (Allen et al 2013). The success of fecal microbiota transplant in curing C. difficile infections further emphasizes the impact of beneficial microbes (van Nood et al 2013).…”
Section: The Futurementioning
confidence: 99%
“…In hospital settings, recognition of the value of beneficial microbes is happening, with use of probiotics to reduce mortality and morbidity of low-birth-weight premature babies (Sawh et al 2016) (including in London, Ontario, after 10 years of advocating) and to prevent antibiotic-associated diarrhea including Clostridium difficile infections (Hickson et al 2007;Maziade et al 2015), albeit not all studies have shown efficacy (Allen et al 2013). The success of fecal microbiota transplant in curing C. difficile infections further emphasizes the impact of beneficial microbes (van Nood et al 2013).…”
Section: The Futurementioning
confidence: 99%
“…Among the microbe-based strategies is the use of probiotics in preterm infants to reduce the risk of necrotizing enterocolitis (Sawh et al 2016). Metabolomics and meta-proteomics are likely to provide useful guidance on microbe-microbe and microbe-host interactions (Mao and Franke 2015;Vernocchi et al 2016).…”
Section: Embracing Colonization Resistancementioning
confidence: 99%
“…Despite many trials that followed, and an overall clear effect of probiotic supplementation on reducing NEC incidence, probiotics were not used at all units. The heterogeneity of organisms and dosing regimens studied have prevented a species-specific treatment recommendation from being made so far [51][52][53][54]. Furthermore, quality control of the available products remains an issue [55].…”
Section: Probioticsmentioning
confidence: 99%